PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN MELALUI DISIPLIN KERJA PADA PT SALIM IVOMAS PRATAMA BALAI JAYA ROKAN HILIR - Afrizal "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at PT Salim Ivomas Pratama Balai Jaya Rokan Hilir. The purpose of this study was to determine the effect of work motivation on employee productivity through work discipline at PT Salim Ivomas Pratama Balai Jaya Rokan Hilir. Work motivation as the independent variable (X) meanwhile work discipline as the intervening variable (Z) and employee productivity as the dependent variable (Y). The problem in this research is the occurrence of fluctuations in the results of CPO production accompanied by a fluctuating decrease in employee absenteeism and also the labor turnover of employees which increases every year as seen from company data and supported by expert opinions. The sample of this study was taken as many as 54 respondents from 119 populations which were calculated using the Slovin formula. The data obtained from the questionnaire results were distributed directly to the field using the Propotionate Stratified Random Sampling technique and then processed and then tested statistically through the SEM SmartPLS 3.3.7 program. From the results of the tests conducted, it shows that work motivation has a positive and significant effect on employee work productivity, work motivation has a positive and significant effect on discipline, work discipline has a positive and significant effect on employee productivity, and work motivation has a positive and significant effect on employee productivity through Work discipline. Keywords: Work Motivation, Work Discipline and Employee Work Productivity.